Hearing Loss After Radiation and Chemotherapy for CNS and Head-and-Neck Tumors in Children. Issue 34 (1st December 2021) - Keilty, Dana; Khandwala, Mohammad; Liu, Zhihui Amy; Papaioannou, Vicky; Bouffet, Eric; Hodgson, David; Yee, Ryan; Cushing, Sharon; Laperriere, Normand; Ahmed, Sameera; Mabbott, Donald; Ramaswamy, Vijay; et al.
Abstract : PURPOSE: Hearing loss (HL) is a serious secondary effect of treatment for CNS and head-and-neck tumors in children. The goal of this study was to evaluate incidence and risk factors for HL in patients with multiple ototoxic exposures. PATIENTS AND METHODS: We evaluated 340 ears from 171 patients with CNS or head-and-neck tumors treated with radiation, with or without chemotherapy, who had longitudinal audiologic evaluation. International Society of Pediatric Oncology-Boston grades were assigned to 2, 420 hearing assessments. Multivariable weighted ordinal logistic regression was fitted to evaluate the effect of clinicopathologic features on HL. RESULTS: Mean cochlea dose (odds ratio [OR] 1.04 per Gy, P < .001), time since radiotherapy (RT; OR 1.21 per year, P < .001), cisplatin dose (OR 1.48 per 100 mg/m 2, P < .001), and carboplatin dose (OR 1.41 per 1, 000 mg/m 2, P = .002) were associated with increasing International Society of Pediatric Oncology-Boston grade of HL. There was no synergistic effect of RT and cisplatin (interaction term, P = .53) or RT and carboplatin (interaction term, P = .85). Cumulative incidence of high-frequency HL (> 4 kHz) was 50% or greater at 5 years after RT if mean cochlea dose was > 30 Gy, while incidence of HL across all frequencies continued to increase beyond 5 years after RT. CONCLUSION: Children treated with radiation and chemotherapy experience a high incidence of HL over time, with associations found between more severe HL and cisplatin or carboplatin dose as well as mean cochlea dose. Mean cochlea dose of ≤ 30 Gy is proposed as a goal to reduce the risk of HL; a lower threshold (20-25 Gy) may be considered in patients receiving platinum chemotherapy to reduce cumulative HL burden.